2013
DOI: 10.1007/s00268-013-2044-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐analysis of Enhanced Recovery After Pancreatic Surgery with Particular Emphasis on Pancreaticoduodenectomies

Abstract: This systematic review suggests that using an ERAS protocol in pancreatic resections may help to shorten hospital length of stay without compromising morbidity and mortality. This seemed to apply to distal pancreatectomy, total pancreatectomy, and PD. Meta-analysis was performed for those studies focusing on PD and showed that there were no differences in readmission or mortality. Morbidity rates were significantly lower for patients managed according ERAS principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
145
6
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(171 citation statements)
references
References 71 publications
(95 reference statements)
5
145
6
11
Order By: Relevance
“…The common outcome derived from the results of many literature studies is that in addition to all contributions of ERAS protocol, it does not change the postoperative mortality rates and duration of rehospitalization [26][27][28][29][30][31]. However, since it requires a robust team work its implementation in every institute or unit is not easy [32].…”
Section: Discussionmentioning
confidence: 99%
“…The common outcome derived from the results of many literature studies is that in addition to all contributions of ERAS protocol, it does not change the postoperative mortality rates and duration of rehospitalization [26][27][28][29][30][31]. However, since it requires a robust team work its implementation in every institute or unit is not easy [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several other fields of surgery have since adopted the ERAS program, achieving better postoperative outcome and decreasing length of postoperative hospitalization [6,7,8,9,10,11,12]. In pancreatic surgery, a recent systematic review and meta-analysis suggested that an ERAS program reduces hospital stay and morbidity for PD [13]. Also, in another study of 145 patients undergoing pancreatic surgery, implementing an ERAS program appeared to be feasible and safe [14].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative enhanced recovery protocols (ERPs) focus on improving surgical outcomes through standardized postoperative fast-track protocols, and were first described in colorectal surgery, urology, and gynecology (9)(10)(11)(12)(13). Surgical goals in patients with lung cancer should include a short trajectory time between diagnosis and surgery, a short hospital stay, and expedited return to daily activities.…”
Section: Original Articlementioning
confidence: 99%